Nuclear phylogenomics, but not mitogenomics, resolves the most successful Late Miocene radiation of African mammals (Rodentia: Muridae: Arvicanthini) - Mikula, Ondřej; Nicolas, Violaine; Šumbera, Radim; Konečný, Adam; Denys, Christiane; Verheyen, Erik; Bryjová, Anna; Lemmon, Alan R; Moriarty Lemmon, Emily; Bryja, Josef (Molecular phylogenetics and evolution, 2021)
The tribe Arvicanthini (Muridae: Murinae) is a highly diversified group of rodents (ca. 100 species) and with 18 African genera (plus one Asiatic) represents probably the most successful adaptive radiation of extant mammals in Africa. They colonized a broad spectrum of habitats (from rainforests to semi-deserts) in whole sub-Saharan Africa and their members often belong to most abundant parts of mammal communities. Despite intensive efforts, the phylogenetic relationships among major lineages (i.e. genera) remained obscured, which was likely caused by the intensive radiation of the group, dated to the Late Miocene. Here we used genomic scale data (377 nuclear loci; 581,030 bp) and produced the first fully resolved species tree containing all currently delimited genera of the tribe. Mitogenomes were also extracted, and while the results were largely congruent, there was less resolution at basal nodes of the mitochondrial phylogeny. Results of a fossil-based divergence dating analysis suggest that the African radiation started early after the colonization of Africa by a single arvicanthine ancestor from Asia during the Messinian stage (ca. 7 Ma), and was likely linked with a fragmentation of the pan-African Miocene forest. Some lineages remained in the rain forest, while many others successfully colonized broad spectrum of new open habitats (e.g. savannas, wetlands or montane moorlands) that appeared at the beginning of Pliocene. One lineage even evolved partially arboricolous life style in savanna woodlands, which allowed them to re-colonize equatorial forests. We also discuss delimitation of genera in Arvicanthini and propose corresponding taxonomic changes.
Keywords: Animals; Databases as Topic; Genetic Loci; databáze jako téma; DNA, Mitochondrial; Genome, Mitochondrial; Rodentia; druhová specificita; Bayesova věta; Cell Nucleus; Anchored phylogenomics; Murinae; Bayes Theorem; Species Specificity; genom mitochondriální; Radiation; Late Miocene; Phylogeny; buněčné jádro; Africa South of the Sahara; mitochondriální DNA; subsaharská Afrika; Tropical Africa; zvířata; Complete mitochondrial DNA; fylogeneze; genetické lokusy